Enhancing the transparency and accountability of state-owned enterprises - Chung-a Park (Asian Development Bank Institute (ADBI), 2020)
This paper provides an overview of national practices for improving the accountability and performance of SOEs by examining relevant legislation, policies, and practices in Asian and other economies. It assesses these against internationally agreed good practices exemplified by the OECD Guidelines on Corporate Governance of State-Owned Enterprises. Nine Asian countries reviewed in this report demonstrate varying degrees of effort and progress in developing and putting in place a legal and regulatory framework for SOE disclosure and transparency. Some have made significant progress in terms of improving information disclosure by SOEs with an accelerated process of corporatization of SOEs and adoption of adequate accounting standards. More and more governments are establishing information reporting systems and performance evaluation systems through which they acquire financial and nonfinancial information from their SOEs. However, some of the reviewed countries lack comprehensive systems for detecting fiscal risk linked to SOEs. A number of SOEs lack an internal audit function for SOEs and/or their financial statements are not systematically subject to independent external audits. At the level of the state, a majority of the countries do not publish aggregate ownership reports, which could potentially limit accountability and restrict the public from overseeing SOE performance. Establishing comprehensive legal and regulatory frameworks for public disclosure of financial and nonfinancial information about the activities of SOEs is critical.
Keywords: L32; L38; G38; 330; corporate governance; state-owned enterprises; disclosure; transparency; accountability; aggregate reporting practices; performance evaluation system